Math, asked by eshatailor19, 11 months ago

x+ y = 3 4x - 3y = 26 by subsubstitution method

Answers

Answered by aryan1234243
3

Step-by-step explanation:

4x+4y=12

4x-3y=26

7y=38

y=38/7

put in first eqn u get urs answer perfectly

Answered by hariommaurya97
2

x  + y = 3 \:  \:  \:  \:  \:  \:  \: eq \: 1

4x - 3y = 26 \:  \:  \:  \:  \:  \: eq2

from equation 1 , we get

x =  (3 - y) \:  \:  \:  \:  \:  \:  \:  \:  \: eq(3)

putting in equation 2

4 (3 - y ) - 3y = 26

12 - 4y - 3y = 26

 - 7y = 26 - 12

 - 7y = 14

y =  - 2

putting y=-2 in equation (3)

x = 3  - ( - 2)

x = 5

Similar questions